Participation and Learning in Community Organizations: A Theoretical Framework - Hleziphi Naomie Nyanungo (Adult Education Research Conference, 2006)
This paper describes a theoretical framework for examining the behavior of community organizations as social actors that shape the participation and learning of their members. The voices of adult educators are among the many scholars and activists calling for local residents to come together to collectively define and address their community concerns. Accompanying the call for participation in collective action is the assumption that through participation, individuals learn to be empowered citizens. Learning in communities is a major focus in adult education (Cunningham, 1996; Hamilton & Cunningham, 1989). However, much of this focus is on the behavior of individuals and less on the behavior of community organizations as sites and vehicles that shape the process and content of learning in the context of communities. In community theory and community development literature, scholars have been primarily concerned with the behavior of individuals or entire communities, but not on the behavior of the community organization, qua organization. Studies on community change generally treat community organizations as tools for change (Bridger, 1992; Gaventa, 1980; Neme, 1997) and not as social actors whose behavior shape the nature of member participation and the process of learning. The behavior of community organizations has also received limited attention in organizational theory and behavior as scholars in this field have primarily focused on bureaucratic organizations (Hall, 1999; Scott, 1998; Selznick, 1966; Zald, 1969). Consequently, there is a need for a framework for examining the behavior of community organizations as it relates to member participation and learning. This paper aims to bring attention to community organizations as social actors shaping the nature of participation and process of learning. Drawing upon community theory, organizational theory, social construction theory and cultural-historical activity theory (CHAT), I present a theoretical framework that is organized in three sections: 1) defining community organizations, (2) examining the behavior of community organizations and (3) investigating participation and learning in community organizations. I conclude the paper with a discussion of the implications of this framework for the field of adult education.